Penanganan Rehabilitasi Medik pada Pasca Artrodesis Kaki Charcot Tanpa Komplikasi - Christina A. Damopolii; Joudy Gessal; Devan Perwira (Universitas Sam Ratulangi, 2023)
Impact of diabetes on the occurrence of Charcot's foot provides conservative treatment to the benefits of arthrodesis. Charcot foot is a debilitating joint disease characterized by progressive multiple bone destruction, dislocations, and severe deformities of the foot and ankle. Its prevalence may increase in the general high-risk population. Initial treatment of Charcot foot is often conservative and involves the use of bracing, casting, and special orthopedic shoes. This intervention allows the patient to functionally ambulate without resorting to more invasive interventions. Arthrodesis is an effective limb-saving method for patients with Charcot neuroarthropathy who have severe deformity and instability. This technique is usually used for chronic cases with irreversible deformity and/or joint instability to increase plantar pressure and balance of the foot and to minimize the risk of foot ulceration and amputation. In conclusion, non-weight bearing treatment dan immobilisation are the most effective rehabilitation management for active-phase Charcot foot accompanied by surgery consideration to maximize the functional of the foot. Keywords: Charcot foot; diabetes; arthrodesis; rehabilitation management Abstrak: Diabetes berdampak terhadap terjadinya kaki Charcot dengan penanganan secara konservatif hingga tindakan artrodesis. Kaki Charcot merupakan salah satu penyakit sendi yang merusak dan ditandai dengan progresifitas kerusakan tulang multipel, dislokasi dan deformitas parah pada kaki dan pergelangan kaki dengan prevalensi yang meningkat pada populasi dengan risiko tinggi. Perawatan awal kaki Charcot seringkali konservatif dan melibatkan penggunaan bracing, casting, dan sepatu ortopedi khusus. Intervensi ini memungkinkan pasien untuk ambulasi secara fungsional tanpa menggunakan intervensi yang lebih invasif. Artrodesis merupakan metode penyelamatan anggota tubuh yang efektif untuk pasien dengan neuropati Charcot yang memiliki deformitas parah dan ketidakstabilan. Teknik ini biasanya digunakan untuk kasus kronis dengan deformitas ireversibel dan/atau ketidakstabilan sendi untuk meningkatkan tekanan dan keseimbangan plantar kaki dan untuk meminimalkan risiko ulserasi dan amputasi kaki. Simpulan studi ini ialah penanganan non-weight bearing dan imobilisasi merupakan penanganan rehabilitasi untuk kaki Charcot fase aktif dengan pertimbangan tindakan pembedahan untuk memaksimalkan fungsi kaki. Kata kunci: kaki Charcot; diabetes; arthrodesis; penanganan rehabilitasi